THE IMPACT OF INTERNATIONALISATION OF HIGHER EDUCATION ON TEACHERS’ PROFESSIONAL COMPETENCES AND SKILLS - Zelenkova, Anna; Spisiakova, Maria (European Scientific Journal, ESJ, 2014)
Internationalisation of higher education in Central Europe has resulted in the offering of university study programmes in foreign languages, most frequently in English. This new situation means a challenge for teachers, administrators and all other stakeholders. The paper focuses on the issues connected with teacher competences to master teaching in specialised courses to international students. Besides the linguistic competence, the authors see the pedagogic and intercultural skills as key factors in shaping the university teacher profile today. The paper also proposes a framework for an in-service teacher training course based on the experience of the authors as teacher trainers. It is meant to be a contribution to the discussion on the necessity to raise teacher competence to teach in an international university environment.